2016
DOI: 10.3390/app6040095
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Unsymmetrical Dimethylhydrazine in Solution and Soil by Bacteria Isolated from Activated Sludge

Abstract: The biodegradation effect and pathway of unsymmetrical dimethylhydrazine (UDMH), which is a major rocket propellant with highly toxic properties, with two strains isolated from the acclimated activated sludge were investigated in solution and in soil. The results demonstrated that Stenotrophomonas sp. M12 (M12) was able to degrade UDMH of 50 mg¨L´1 as the sole carbon source in aqueous mineral salt medium (MSM), but could not degrade UDMH in soil. Comamonas sp. P4 (P4) barely degraded UDMH of 50 mg¨L´1 as the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…To date, several conventional technologies have been attempted to remove UDMH. Liao et al 4 reported bacteria belonging to Stenotrophomonas sp. and Comamonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several conventional technologies have been attempted to remove UDMH. Liao et al 4 reported bacteria belonging to Stenotrophomonas sp. and Comamonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…After launch, burned‐out rocket stages fall at the distance ≤1500 km from a launchpad [2], such as Baikonur (Kazakhstan), resulting in contamination of the environment with ≤4 tons of unburned fuel [3–5] in the case of a successful launch and ≤600 tons in the case of an accident [6]. Under the effect of NO 2 , oxygen, sunlight, elevated temperatures, biota, soil, and water constituents [7–9], UDMH transforms into a number of potentially dangerous substances – amines, nitrosoamines, triazoles, pyrazoles, and amides [10,11]. Among all known UDMH transformation products (TPs), the most studied are amines, nitrosoamines, and formamides [12–15].…”
Section: Introductionmentioning
confidence: 99%